2013
DOI: 10.1096/fj.13-232041
|View full text |Cite
|
Sign up to set email alerts
|

Insight into structure‐function relationship in phenol‐soluble modulins using an alanine screen of the phenol‐soluble modulin (PSM) α3 peptide

Abstract: Phenol-soluble modulins (PSMs) are a family of peptides with multiple functions in staphylococcal pathogenesis. To gain insight into the structural features affecting PSM functions, we analyzed an alanine substitution library of PSMα3, a strongly cytolytic and proinflammatory PSM of Staphylococcus aureus with a significant contribution to S. aureus virulence. Lysine residues were essential for both receptor-dependent proinflammatory and receptor-independent cytolytic activities. Both phenotypes also required a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 39 publications
(77 reference statements)
6
94
0
Order By: Relevance
“…The amino acids of the N-terminus in PSMα2 1-16 are identical to those in PSMα2 1-5 and PSMα2 1-10 , respectively, yet the peptides activate different receptors. It is known from earlier studies that the binding pocket in FPR1 has room for no more than five amino acids [15], and when the charge of an FPR1 selective pentapeptide is reduced, such peptides will interact also with FPR2 [31], even if FPR1 is still the preferred receptor [32]. This means that receptor preference is not determined solely by the amino acids that have access to the presumed agonist binding pocket of the receptor, but in part also by amino acids in the peptide that do not have direct access to the binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acids of the N-terminus in PSMα2 1-16 are identical to those in PSMα2 1-5 and PSMα2 1-10 , respectively, yet the peptides activate different receptors. It is known from earlier studies that the binding pocket in FPR1 has room for no more than five amino acids [15], and when the charge of an FPR1 selective pentapeptide is reduced, such peptides will interact also with FPR2 [31], even if FPR1 is still the preferred receptor [32]. This means that receptor preference is not determined solely by the amino acids that have access to the presumed agonist binding pocket of the receptor, but in part also by amino acids in the peptide that do not have direct access to the binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Our results obtained using PSMα2 variants suggest that the full-length peptide is required for cytolytic activity on apoptotic neutrophils, but since the N-terminus is the part that is essential for neutrophil activation there is no direct link between the cytolytic and the proinflammatory activities. The lack of cytolytic activity of the C-terminal truncated peptides may be related to a reduced capacity to form a α-helix, although it has been suggested that the α-helicity is not correlated with peptide functions, including cytolytic activity [31]. In line with our findings, a recent study using an alanine substitution screen of PSMα3, a closely related S. aureus modulin, demonstrates that the physicochemical property of the amino acids present in C-terminus of PSMα3 (i.e., Lys6, Lys12, Lys17, Asn21 or Asn22) is crucial for the FPR2 binding capacity [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSMs can be classified according to their length as ␣-PMSs (20 to 25 amino acids), and ␤-PSMs (43 to 45 amino acids). S. aureus expresses four ␣-PSM peptides encoded in the ␣ psm locus, two ␤-PSM peptides encoded in the ␤ psm locus, and the ␦-toxin encoded within RNAIII, the effector molecule of the Agr system (48). These peptides are exported by an ATP-binding cassette (ABC) transporter with two separate membrane components (PmtB and PmtD) and two separate ATPases (PmtA and PmtC) (49).…”
Section: Amyloid Structures With Dedicated Fiber Assembly Machinerymentioning
confidence: 99%
“…In view of lysine, the high content of lysine negatively influenced the uptake of arginine in vivo (Wu and Meininger, 2002). Lysine residues were essential for both receptor-dependent proinflammatory and receptor-independent cytolytic activities (Cheung et al, 2014). In comparison, the results for the composition of essential amino acid in J. sigillata and J. regia from China were consistent with several published reports including those for Spanish almonds (Calixto et al, 1981), New Zealand hazelnuts (Savage and McNeil, 1998), Turkish Tombul hazelnut (Alasalvar et al, 2003), Chilean hazelnut (Villarroel et al, 1987), almond, pecan, pine nut, and pistachio (Ruggeri et al, 1998).…”
Section: Compositions Of Essential Amino Acidsmentioning
confidence: 99%